A new scalarizing approach and the semicontinuities of the solution mapping of a parametric vector quasi-equilibrium problem - Phạm, Hữu Sách (Trường Đại học Đà Lạt, 2014)
This paper gives sufficient conditions for the upper and lower semicontinuities of the solution mapping of a parametric vector quasi-equilibrium problem with moving cones. We use a new scalarizing approach quite different from traditional linear scalarization approaches. The main tool of this paper is a new notion of nonlinear scalarization function which is a generalized version of the Gerstewitz function applied to set-valued maps.